CAAD in Mimari Eğitime Entegre Edilmesi - Elhardudi, Mahmod M. A. (İstanbul Kültür Üniversitesi / Fen Bilimleri Enstitüsü / Mimarlık Anabilim Dalı, 2007)
CAAD, tasarım sürecinde kullanılan bütün programların dahil olduğu (örn. Taslak, tasarım, sunum, iletişim, vs.) Bilgisayar Destekli Mimari Tasarım demektir. Bu tez, CAAD'ın mimari eğitime entegre edilme olasılığını tartışır. Bu tezin temel soruları şunlardır; niye CAAD'ı öğretmek, CAAD eğitime nasıl katkı sağlayabilir? CAAD'ı ne zaman öğretmeye başlamak? Hangi aşamada CAAD öğretilebilir ve ne derecede entegre edilmelidir? Ne öğretilecek, hangi uygulamalar eğitim sürecine yardımcı olabilir? CAAD eğitime nasıl entegre edilebilir? Tez beş bölüme ayrılmıştır. İlk bölüm, mimaride kullanılan bilgisayar programları konseptini inceler, aynı zamanda bu tezin amaçları ve stratejisi de incelenmektedir. İkinci, üçüncü ve dördüncü bölümler bu tezin yapısını oluşturmaktadır. İkincisi, CAAD'ın gelişim tarihini ve bu aracın faydalarını içerir. Üçüncü bölüm, CAAD'ın hem mimari eğitim hem de araştırmalardaki konumunu inceler. İncelemelere ek olarak CAAD öğretiminde değişen kurallar dahildir. Dördüncüsü, CAAD entegrasyonunun gerekleri ve teorisini tartışır. Son olarak, beşinci bölüm bu çalışmanın temel bulgularını ve gelecekle ilgili bazı önerileri içeren sonuç bölümüdür.

CAAD refers to Computer Aided Architectural Design which includes all computer programs that used in design process (e.g. drafting, design, presentation, communication, etc.). At first the concept CAD (Computer Aided Design) was used to refer to all computer programs that used in drawing and design. Quickly, CAD was replaced by CAAD (Computer Aided Architectural Design) which expressing the specific character of computer applications that related to architecture field. By the end of 1980s another concept has appeared that is IT (Information Technology). During 1990s, this concept was replaced by ICT (Information and Communications Technology) which representing the current values of computing and digital technology of our era. This thesis argues the possibility of integrating CAAD into architectural education. The main questions of this thesis are; why to teach CAAD, what values that CAAD can add to education? When to start teaching CAAD? In which stage should CAAD be taught and to what extent should it being integrated? What to teach, which applications can be helpful to education process? And how CAAD can be integrated into the education? Thesis divided into five chapters. First chapter reviews the concepts that refer to computer programs used in architecture, also the aims of this thesis and strategy of it. Second, third and fourth chapter form the body of the thesis. Second one includes the history of developing CAAD and utilities of this tool. The third chapter reviews the situation of CAAD in both architectural education and researches. In addition to reviews the changing rules in teaching CAAD. Fourth one discusses the theories and the requirements of integrating CAAD. Finally, the fifth chapter is the conclusion which includes the main findings of this study and some future recommendations.
Integrating CAAD Into Architectural Education
Keywords: Mimarlık; Architecture